KEPRAKTISAN MEDIA PEMBELAJARAN INTERAKTIF NEARPOD PADA PEMBELAJARAN IPAS MATERI PERUBAHAN BENTUK ENERGI KELAS IV - Olaini, Dina Nur; Hunaifi, Abdul Aziz; Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
IPAS is an integration of Natural Sciences (IPA) and Social Sciences (IPS), introduced through the implementation of the Merdeka Curriculum. This integration aims to facilitate students in understanding surrounding phenomena—both in natural and social environments—in a comprehensive and contextual manner. However, IPAS learning is often abstract and difficult for students to grasp, especially when delivered using conventional media. Therefore, there is a need for innovative learning media that can support students' understanding in a more interactive and engaging way. This study aims to determine the practicality level of using Nearpod interactive learning media in IPAS learning, specifically on the topic “Changes in Forms of Energy” for Grade IV students at SD Negeri Tiron 4. The research employed a descriptive quantitative method with data collection carried out through questionnaires distributed to teachers and students after the learning process using the Nearpod platform. The questionnaire was designed to measure perceptions of ease of use, effectiveness, and the attractiveness of the media in supporting the learning process. The data analysis results show that the Nearpod interactive learning media achieved a very high level of practicality, with a score of 92% based on teacher responses and 92.7% based on student responses. These findings indicate that Nearpod strongly supports the integrative and interactive nature of IPAS learning. According to the practicality criteria proposed by Akbar (2015), this media falls into the category of